PERLINDUNGAN KONSUMEN TERHADAP PENGGUNA PRODUK KOSMETIK YANG MENGANDUNG BAHAN BERBAHAYA (STUDI KASUS PEREDARAN PRODUK KOSMETIK BAHAN BERBAHAYA DI KECAMATAN ULEE KARENG KOTA BANDA ACEH) - Herni Ayu Sari; Nila Trisna (LPPM Universitas Ekasakti Padang, 2023)
This study aims to determine consumer protection against the circulation of cosmetics containing hazardous materials in Ulee Kareng District, Banda Aceh City. To find out how to protect consumers against the use of cosmetic products containing dangerous ingredients in Ulee Kareng sub-district, Banda Aceh city and efforts to resolve disputes against consumers as a result of the use of cosmetics containing hazardous ingredients. This research was conducted to collect data at the BPOM Aceh office and YAPKA using interviews and documentation techniques. The data analysis method used is descriptive in nature, which requires direct interviews and documentation by analyzing data related to research. The results of the study show that legal protection for consumers for the distribution of cosmetics containing hazardous ingredients to the detriment of consumers is carried out by each element involved based on Law No. 8 of 1999 concerning Consumer Protection and BPOM RI Regulation No. HK.00.05.4.17.45 concerning Cosmetics. There are 2 responsibilities for business actors for the circulation of cosmetics that harm consumers, namely first in the form of administration, namely compensation in the form of refunds and second in the form of punishment, namely confinement or imprisonment.